Functional relationships between gaze behavior and movement kinematics when performing high bar dismounts - an exploratory study - Heinen, T.; Velentzas, K.; Vinken, P. M. (Human Movement, 2012)
Purpose. The aims of this study were, first, to investigate visual spotting and, second, to explore the functional relationships between movement structure and gaze behavior in gymnasts as they perform preparatory giant swings (traditional and scooped technique) and dismounts (single straight and double tucked salto) with increasing difficulty on the high bar. It was predicted that visual spotting would occur in all experimental tasks. Methods. Relationships between gaze behavior and movement kinematics were explored to provide a clearer picture of how gaze is interconnected with the kinematics of dismounts on the high bar. For this purpose, kinematic parameters were measured with an optical movement-analysis system while gaze behavior was measured by using a portable and wireless eye-tracking system. Results. The measurement of gaze behavior revealed that gymnasts use visual spotting in all three tasks showing fixations throughout the whole movement. Each task was furthermore characterized by a sequence of visual fixations that was thought to serve specific movement goals. In particular, fixations during the downswing phase of the preparatory giant swings were significantly correlated with the movement phases when beginning the hip extension and flexion in the "kick through" as well as with the athlete`s distance of flight during the dismounts. Conclusions. The findings suggest that gymnasts can use visual spotting during preparatory giant swings and dismounts on the high bar and that there are functional relationships between different fixations and specific movement goals.